International Strategy of French Wine Company within a Global Wine Market - Daniel, Clément Quentin; Král, Petr, 1979-; Tisovski, Marija; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2014)
The objective of the thesis is to investigate how a wine company plays on a globalized wine market and what are the adopted strategies in order to penetrate new markets. Some recommendations will be provided in order to improve the company's presence. In this perspective two different markets will be analyzed: American and Chinese. For both markets we highlighted the main trends of consumption, the national production and competition. Moreover we described how the chosen company penetrated these markets, what are the stakes for the enterprise. The French wine market suffers since 1960's and its consumption is going down every year. From this assessment French wine companies try to develop their activities abroad and reach new markets. The US market is the largest in the world in term of consumption in volume. The Chinese wine market is rather new but faces an incredible increase. The potential on both markets are substantial.
Vedoucí práce: Petr Král
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses